Propuesta de reforma al proceso de curaduría especial por segundas nupcias en garantía del principio de celeridad de las partes - Álava Toala, Jairo Antonio (2018)
The present investigation entitled: "Proposal of reform to the process of special curatorship by second nuptials in guarantee of the principle of celerity". The current work arises from the need to propose the reform of the special curatorship process in order to guarantee the principle of speed, in order to perfect this procedure in favor of the interested parties and that require the protection of their minor children before to get married. The general objective of the present investigation consists in the proposal of reform to the process of special Curaduría by second nuptials in guarantee of the principle of celerity of the parts, and to achieve the objectives in the present study it was made use of the methods of investigation: qualitative and quantitative, as well as analytical and statistical, by means of which the results were analyzed and also the conclusions and recommendations made. The research tools and techniques were applied, such as: The interview and the survey, which were applied by judges, judges and people specialized in the subject for the verification of the hypothesis of the present study……….